Pharmacological, and Community Determinants of Iron Deficiency Anemia in Reproductive-Age Women: A Multi-Level Study in Urban Slums of Karachi - Saqib Nabi Khuhro, Kiran Khan, Aftab Hussain Abro, Anjum Rehman, Ata Ur Rehman, Muhammad Aitmaud Uddolah Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Iron deficiency anemia (IDA) is a most common nutritional problem in women of child bearing age in resource poor urban areas. It is affected by a host of pharmacologic, dietary and environmental factors. Objective: To determine the prevalence and identify pharmacological and community determinants of iron deficiency anemia among reproductive-age women. Methods: This was a cross-sectional analytical study with data collected over a period of one year (January 2022-January 2023) at Tertiary Care Hospital of Karachi. The study involved 72 women between the ages of 18 and 45 years (using non-probability consecutive sampling method). Participants were asked questions about socio-demographic, diet, medication, reproductive and community factors via a questionnaire. Iron deficiency anemia was diagnosed based on hemoglobin and serum ferritin. IBM SPSS Statistics version 25 was used for data analysis. The chi-square test was used to examine associations with p ≤ 0.05 and multivariate logistic regression was used to determine independent predictors, with p ≤ 0.05 Results: The prevalence of iron deficiency anemia was 63.9%. Moderate anemia was the most common form. Poor dietary intake, low use of iron supplementation, and inadequate sanitation were significantly associated with anemia (p < 0.05). Multivariate analysis showed that poor diet (AOR = 3.8), lack of iron supplementation (AOR = 2.6), and poor sanitation (AOR = 2.9) were independent predictors of iron deficiency anemia. Conclusion: Iron deficiency anemia is highly prevalent among reproductive-age women and is strongly influenced by nutritional, pharmacological, and environmental factors. Multi-level interventions focusing on dietary improvement, increased supplementation, and enhanced community health conditions are essential to reduce its burden. Keywords: Iron Deficiency Anemia, Women, Nutrition, Iron Supplementation, Public Health, Sanitation